The relationship between parental food parenting practices & child eating behavior: A comparison of mothers and fathers - Vollmer, Rachel L. (Appetite, 2021)
The objective of this study was to compare the relationships between food parenting practices and child eating behavior among mothers and fathers of young children. This cross-sectional study recruited mothers (n = 127) and fathers (n = 118) of children (4.2 ± 1.3 years old) to complete surveys (face-to-face and online). Each parent completed the Comprehensive Food Parenting Questionnaire, Children's Eating Behavior Questionnaire, and demographic questions. Linear regressions were used to compare the relationships between parental food parenting practices and children's eating behaviors with parent sex as a moderator. Child age and sex served as control variables in each regression. Parent sex was a significant moderator in several relationships between parent food parenting practices and child eating behavior. In the relationship between parental restriction for health (ß = -.14, p = .014) and monitoring (ß = -.13, p = .028) and child slowness in eating, the slope of the interaction was significantly higher for mothers, meaning that when mothers and fathers use the same level of restriction for health and monitoring, child slowness in eating is higher for children of mothers. When mothers and fathers used the same level of restriction for weight, child food responsiveness (ß = .13, p = .003) and emotional overeating (ß = .12, p = .046) was significantly higher for children of fathers. There may be differences in how mothers and fathers implement food parenting practices and/or differences in how these practices impact children. Specifically, for fathers, it seems that the use of restriction for weight is more detrimental for children's eating behaviors compared to when mothers use the same level of restriction for weight.